If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + -4 = 8 + 7n Reorder the terms: -4 + 4n = 8 + 7n Solving -4 + 4n = 8 + 7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7n' to each side of the equation. -4 + 4n + -7n = 8 + 7n + -7n Combine like terms: 4n + -7n = -3n -4 + -3n = 8 + 7n + -7n Combine like terms: 7n + -7n = 0 -4 + -3n = 8 + 0 -4 + -3n = 8 Add '4' to each side of the equation. -4 + 4 + -3n = 8 + 4 Combine like terms: -4 + 4 = 0 0 + -3n = 8 + 4 -3n = 8 + 4 Combine like terms: 8 + 4 = 12 -3n = 12 Divide each side by '-3'. n = -4 Simplifying n = -4
| -n-1/2=10 | | 0=18x+1 | | 2(4x-15)=3(x-15) | | 2x+10=5+3x | | 7a+16-3a=-44 | | 9+10a=10 | | (x-2)=3(x-3) | | (X)=2(1+3) | | 2(4x-15)=3(x+15) | | 3+3p=6 | | 4a+12=7 | | 4(x-9)=x-15 | | 4(y-8)=8 | | m/3-6 | | 8h^2-50= | | 4/9:134/72 | | 9+3y-2yt=14 | | x(2x+7)= | | 11-8b=-5-4b | | 4a+12=-16 | | 4(y-4)=2(y+25)-4 | | 10x-18=x+63 | | 5Y+9=8Y-6 | | -8+9n=10 | | 7m-6=-104 | | 7x+60=x+60 | | (4x^2+4x+1)-(4x^2+2)=8x+16 | | 3-(5x-1)/10=(x-1)/5-(x-3)/2 | | 5r=-1 | | 5r=-2 | | 7-6a=1-4a+a | | 4u+13=65 |